A Phase 2 exploratory trial of Paired Reading in Spanish language in Colombia. (2021) - Thurston, Allen; Bernal Nisperuza, Gloria Lucia; Abadía Alvarado, Luz Karime; Cockerill, Maria; MacKenzie, Alison; O'Keeffe, Joanne; Garcia Ospina, Juan Manuel; Garcia, Pelusa Orellana
Highlights: A protocol for a Phase 2 randomised controlled trial in reading. Peer tutoring will be assessed for efficacy in Colombian schools. The technique of paired reading is described. Research design issues are explored. Abstract: There is good evidence that peer tutoring, when used in a structured manner can lead to attainment gains in English reading. Transferability of the technique to other languages and educational contexts are less well studied. This is a protocol for a Phase 2 exploratory trial designed to establish if peer tutoring, in the form of Paired Reading can transfer to the Colombian education system, and into the Spanish language. The protocol establishes success criteria to determine whether there is enough evidence of efficacy to warrant a Phase 3 definitive trial of the technique and will determine likely effects on Spanish reading attainment to help design a Phase 3 trial.